The taxonomic separateness of the species Aporophyla lueneburgensis (Freyer, 1848) and Aporophyla lutulenta ([Denis & Schiffermüller], 1775) occurring in Poland (Lepidoptera: Noctuidae) - Janusz Nowacki; Oscar Mahecha-J.; Roman Wasala; Anna Zubek (SHILAP)
Morphological and genetic comparisons were carried out of specimens of two sister species Aporophyla lueneburgensis (Freyer, 1848) and Aporophyla lutulenta ([Denis & Schiffermüller], 1775), which are distributed allopatrically in Poland. The specimens from different populations of these two species hardly differ morphologically but do differ genetically. The mean genetic distance between the groups of A. lueneburgensis and A. lutulenta examined here indicates that their geographic populations can be treated as belonging to separate species. Hence, A. lueneburgensis and A. lutulenta occurring in Poland can be regarded as two separate but sister species.